2005
DOI: 10.1021/bm0493234
|View full text |Cite
|
Sign up to set email alerts
|

Ionic, Structural, and Temperature Effects on DNA Nanoparticles Formed by Natural and Synthetic Polyamines

Abstract: We synthesized analogues of spermine and studied the effects of chemical structure, ionic strength, and temperature on lambda-DNA nanoparticle formation. Effective concentration of polyamines for DNA condensation (EC50) was lowest for hexamines (0.2 microM) and highest for spermine (tetramine, 4.2 microM). The EC50 value increased with [Na+]. Dynamic light scattering showed nanoparticles with hydrodynamic radii (R(h)) of 40-50 nm. Effect of temperature on R(h) was measured between 20 and 70 degrees C. For sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 65 publications
3
37
0
Order By: Relevance
“…Similarly, Vijayanathan et al reported that spermine-like polyamines were stabilized in the major groove of DNA. 26) Our molecular dynamics studies also showed that a 600 Da branched PEI binds to 4 base pairs in the major groove of DNA. 32) This corresponds to l=8, which was the parameter used in excluded site model in this study.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Similarly, Vijayanathan et al reported that spermine-like polyamines were stabilized in the major groove of DNA. 26) Our molecular dynamics studies also showed that a 600 Da branched PEI binds to 4 base pairs in the major groove of DNA. 32) This corresponds to l=8, which was the parameter used in excluded site model in this study.…”
Section: Discussionsupporting
confidence: 51%
“…The excitation and emission monochromators were set to 480 nm, and the scattered light was measured at 90° angle with respect to the incident beam. 26) PEI solution was added to 30 μM DNA in TAE buffer at room temperature (25±2°C) so that it became the same N/P ratio as the ITC study and the measurements were repeated.…”
Section: Itc Model Fittingmentioning
confidence: 99%
“…At the low salt concentrations used here, 10 mM Tris, pH 7.5, the binding of most tetra- and higher valent ions is close to stoichiometric (35). None-the-less, Thomas and coworkers (36, 45) at similar low salt conditions have found that considerably more tetra-lys 4+ was necessary for DNA condensation than spermine 4+ and that significantly more penta-lys 5+ was necessary than several +5 analogs of spermine. Brewer et al (46) reported that hexa-arg 6+ is much more effective than hexa-lys 6+ at condensing DNA.…”
Section: Discussionmentioning
confidence: 98%
“…The ability of polyamines and their analogues to promote conformational changes within DNA and its condensation to nanoparticles can facilitate the transport of oligonucleotides through the cell membrane and be helpful in developing simple carrier systems for gene delivery [ 17 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%